Novel methodology based on biomimetic superhydrophobic substrates to immobilize cells in hydrogel spheres for tissue engineering applications - Lima, A. C. (2012)
The low retention/integration of injected cells by host structures represents an important challenge in cell based therapies for regenerative medicine purposes. Cell immobilization in hydrogels for target cell delivery has been developed to circumvent this issue. However, the existing immobilization methodologies sometimes have several steps under wet conditions and present some drawbacks, including poor encapsulation efficiency and the use of harmful conditions for cells or other fragile molecules, such as proteins or growth factors. In order to surpass these problems mesenchymal stem cells isolated from rats (rMSCs) bone marrow and fibronectin (FN) were immobilized in alginate beads to mimic extracellular matrix environment using an innovative approach involving the jellification of the liquid precursor droplets onto superhydrophobic surfaces. The alginate drops with cells and FN hardened very fast, at room temperature, into hydrogels spheres in an isolated environment which avoided the loss of FN and any contamination or exchange of molecules with other liquid phase. The process for particle fabrication employed allowed a very high efficiency on FN encapsulation and also the mild conditions prevented the loss of cell viability. Encapsulated rMSCs remained viable and were slowly released from the beads during more than 20 days.